9-1-1 Triage of Non-Traumatic Chest Pain: Association with Hospital Diagnosis. (4th July 2017) - Scott, Greg; Clawson, Jeff J.; Gardett, Isabel; Broadbent, Meghan; Williams, Nathan; Fivaz, Conrad; Marshall, Gigi; Barron, Tracey; Olola, Christopher
Abstract: Objective : Chest pain is one of the most common reasons people seek emergency care—and one of the most critical. In the United States, chest pain is the second most common reason for emergency department (ED) visits. A patient's primary complaint of "chest pain" may reflect a broad range of underlying causes; therefore, it is important that emergency medical service (EMS) agencies gain a thorough understanding of these cases, beginning with the initial management of chest pain in the 9-1-1 center. The primary objective of this study was to compare hospital-confirmed patient discharge diagnoses to all calls handled by emergency medical dispatchers (EMDs) using the Chest Pain/Chest Discomfort (Non-Traumatic) Chief Complaint Protocol.Methods : The retrospective descriptive study utilized emergency medical dispatch, EMS, and hospital datasets, collected at two emergency communication centers in North America, from January 1, 2013 to December 31, 2014. Patients who were dispatched using the Chest Pain/Chest Discomfort Chief Complaint Protocol and matched to hospital datasets were included. The primary outcome was the number and percentage of cases classified as ischemic heart disease (IHD), other cardiac-related conditions, or non-cardiac-related conditions associated with chest pain. We also evaluated the distribution of causes of chest pain across demographic indicators and dispatch determinants.Results : 3, 007 cases were identified as "chest pain" at dispatch for which corresponding hospital records were identified. Cases in the study were obtained by linking EMS/Hospital and Emergency Medical Dispatch datasets. Of these cases, 47.1% (n = 1, 417) were due to cardiac-related causes of chest pain, 61.5% of which were Ischemic Heart Disease (IHD), while the rest had other cardiac-related causes. Of the IHDs, 32.1% were Acute Myocardial Infarction (AMI).Conclusions : Underlying causes of non-traumatic chest pain reported to 9-1-1 demonstrate a wide range of etiologies, with a mix similar to that of chest pain patients in several other healthcare settings, including hospital emergency departments. Most IHD events are triaged by EMDs to the (highest) DELTA priority level, while the CHARLIE level captures nearly all of the remaining IHD cases.